Improving Point-of-Care Ultrasound Documentation and Billing Accuracy in a Pediatric Emergency Department - Ng, Carrie (Pediatr Qual Saf, 2020)
OBJECTIVE: The performance and interpretation of point-of-care ultrasound (POCUS) should be documented appropriately in the electronic medical record (EMR) with correct billing codes assigned. We aimed to improve complete POCUS documentation from 62% to 80% and improve correct POCUS billing codes to 95% or higher through the implementation of a quality improvement initiative. METHODS: We collected POCUS documentation and billing data from the EMR. Interventions included: (1) staff education and feedback, (2) standardization of documentation and billing, and (3) changes to the EMR to support standardization. We used P charts to analyze our outcome measures between January 2017 and June 2018. RESULTS: Six hundred medical records of billed POCUS examinations were included. Complete POCUS documentation rate rose from 62% to 91%, and correct CPT code selection for billing increased from 92% to 95% after our interventions. CONCLUSIONS: The creation of a standardized documentation template incorporated into the EMR improved complete documentation compliance.